Molecular cloning of avian myelocytomatosis virus (MC29) transforming sequences. - Lautenberger, J A (1981)
Avian myelocytomatosis virus (MC29), a defective acute leukemia virus, has a broad oncogenic spectrum in vivo and transforms fibroblasts and hematopoietic target cells in vitro. We have used recombinant DNA technology to isolate and to characterize the sequences that are essential in the transformation process. Integrated MC29 proviral DNA was isolated from a library of recombinant phage containing DNA from the MC29-transformed nonproducer quail cell line Q5. The cloned DNA was analyzed by Southern blotting of restriction endonuclease digests and by electron microscopic visualization of R loops formed between the cloned DNA and MC29 or helper virus RNA. It was found that the 9.2-kilobase cloned DNA insert contains approximately 4 kilobases of viral sequences and 5.2 kilobases of quail cellular sequences. The viral sequences contain all of the MC29-specific sequences and 5' helper-related sequences as well as part of the envelope region. The size of the cloned EcoRI fragment is the same as that of the major band in EcoRI-cleaved Q5 DNA that hybridizes to viral sequences. Transfection of the cloned DNA into NIH 3T3 cells revealed that the MC29-specific sequences are functional in that they induce foci of transformed cells with high efficiency.